Coprime, infinitely

Let a n = 2 n + 3 n + 6 n + 1 ( n N + ) a_{n}=2^{n}+3^{n}+6^{n}+1(n\in \mathbb{N}^{+}) .

Find the smallest integer k 2 k\ge 2 such that g c d ( k , a n ) = 1 gcd(k,a_{n})=1 forall n N + n\in \mathbb{N}^{+} . (Give your answer as 0 if there is no such k . )


The answer is 23.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Patrick Corn
May 30, 2018

Since a n = ( 2 n + 1 ) ( 3 n + 1 ) , a_n = (2^n+1)(3^n+1), if k k is coprime to all a n , a_n, then for any prime p k , p|k, we have that 2 n 1 2^n \equiv -1 mod p p has no solution, and 3 n 1 3^n \equiv -1 mod p p also has no solution.

It's not hard to check by hand or by computer that p = 23 p=23 is the smallest prime for which this is true. (To see that it is true for p = 23 , p=23, note that 2 2 and 3 3 are squares mod 23 23 and 1 -1 is not, by various applications of quadratic reciprocity .) So the smallest possible prime dividing k k is 23 , 23, and hence the smallest k k is 23 . \fbox{23}.

Please elaborate the statement you wrote in brackets.

Atomsky Jahid - 3 years ago

Log in to reply

Well, 2 2 is a square mod p p if and only if p ± 1 p \equiv \pm 1 mod 8 8 (the "second supplement"). And 1 -1 is a square mod p p if and only if p 1 p \equiv 1 mod 4 4 (the "first supplement"). And ( 3 23 ) = ( 23 3 ) = ( 2 3 ) = 1 \left( \frac3{23} \right) = -\left(\frac{23}3 \right) = -\left(\frac23 \right) = 1 (in general for prime p > 3 , p >3, 3 3 is a square mod p p if and only if p ± 1 p \equiv \pm 1 mod 12 12 ).

Patrick Corn - 3 years ago
Haosen Chen
Jun 2, 2018

Obiviously,the smallest one must be a prime (if it exists). And k 2 , 3 k≠2,3 ,since a 1 = 12 a_{1}=12 .

Let r n ( m o d ( p 1 ) ) , 0 r p 2 r\equiv n(mod (p-1)),0\le r\le p-2 ,here p 5 p\ge 5 is prime.By Fermat's little theorem, 2 p 1 1 ( m o d p ) , 3 p 1 1 ( m o d p ) , 6 p 1 1 ( m o d p ) 2^{p-1}\equiv 1(modp),3^{p-1}\equiv 1(modp), 6^{p-1}\equiv 1(modp) .Thus,If p ( 2 n + 3 n + 6 n + 1 ) p|(2^{n}+3^{n}+6^{n}+1) ,then p ( 2 r + 3 r + 6 r + 1 ) p|(2^{r}+3^{r}+6^{r}+1) .

That is equivalent to: if p ( 2 r + 3 r + 6 r + 1 ) p\nmid (2^{r}+3^{r}+6^{r}+1) ,then p ( 2 n + 3 n + 6 n + 1 ) p\nmid (2^{n}+3^{n}+6^{n}+1) .

Besides, p ( 2 r + 3 r + 6 r + 1 ) p|(2^{r}+3^{r}+6^{r}+1) \Rightarrow p 6 p 1 r ( 2 r + 3 r + 6 r + 1 ) p|6^{p-1-r}(2^{r}+3^{r}+6^{r}+1) \Rightarrow p ( 3 p 1 r 2 p 1 + 2 p 1 r 3 p 1 + 6 p 1 + 6 p 1 r ) p|(3^{p-1-r}\cdot2^{p-1}+2^{p-1-r}\cdot 3^{p-1}+6^{p-1}+6^{p-1-r}) \Rightarrow p ( 3 p 1 r + 2 p 1 r + 1 + 6 p 1 r ) p|(3^{p-1-r}+2^{p-1-r}+1+6^{p-1-r}) ,which means that we only need to check the case when r = 1 , 2 , . . . , p 1 2 r=1,2,...,\frac{p-1}{2} .

When p=5, p ( 2 2 + 3 2 + 6 2 + 1 ) p|(2^{2}+3^{2}+6^{2}+1) ; when p=7, p ( 2 3 + 3 3 + 6 3 + 1 ) p|(2^{3}+3^{3}+6^{3}+1) ; when p=13,17,19, p ( 2 p 1 2 + 3 p 1 2 + 6 p 1 2 + 1 ) p|(2^{\frac{p-1}{2}}+3^{\frac{p-1}{2}}+6^{\frac{p-1}{2}}+1) ; when p=23,it is not hard to check that 23 ( 2 j + 3 j + 6 j + 1 ) ( j = 0 , 1 , . . . , 11 ) 23\nmid(2^{j}+3^{j}+6^{j}+1)(j=0,1,...,11) ,while a wiser way is stated by sir Patrick Corn.

So the answer is 23 \boxed{23} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...